Rhabdomyolysis Induced by Nonstrenuous Exercise in a Patient with Graves’ Disease - Sarawut Summachiwakij; Issac Sachmechi (Case Reports in Endocrinology)
Hyperthyroidism can result in several musculoskeletal conditions such as thyrotoxic periodic paralysis, thyrotoxic myopathy, and thyroid ophthalmopathy. Rhabdomyolysis has been rarely reported to be associated with hyperthyroidism. We describe a 33-year-old man who presented with bilateral thigh pain and dark brown urine after regular squatting. He had a past medical history of hyperthyroidism but stopped taking it 2 months prior to admission. He was found to have rhabdomyolysis, myoglobinuria, and thyrotoxicosis. Presence of thyroid-stimulating immunoglobulins (TSI) and high radioiodine uptake confirmed a diagnosis of Graves' disease. He received aggressive fluid resuscitation and sodium bicarbonate intravenously along with monitoring fluid and electrolyte. Methimazole was also resumed. The patient responded to treatment and rhabdomyolysis gradually resolved. Therefore, nonstrenuous exercise can potentially induce rhabdomyolysis in patients with hyperthyroidism. Although hyperthyroidism is not widely recognized as a cause of rhabdomyolysis, it should be considered in the differential diagnosis of rhabdomyolysis.